Popularizing the Gay Characters: A Study of American Gay-Themed TV Series in 2000s - Rudy Rudy; Muhammad Kiki Wardana (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
This study is a qualitative research which concentrates on the rise of TV series gay characters on American televisions starting in the early 2000s. The emergence of gay TV series in 2000s has made this phenomena interesting as well as essential to discuss since American television in the pre 2000s era was not not open about the gay characters in television series. The data for this study were obtained through a literature review consisting of journal articles as well as books. This study intended to identify why gay-themed TV series appeared in the 2000s by applying Hall’s theory of representation as a way for analyzing. This research is useful to an additional reference for other researchers and to increase people’s understanding on the gay TV series phenomenon in the US. The research findings showed that there at least four representations explaining the reasons for the emergence of gay-themed TV series in America – the progress of science and knowledge, the strength of minority, the state support, and the new target consumers.